A knowledge-oriented, context-sensitive architectural framework for service deployment in marginalized rural communities - Thinyane, Mamello P (Rhodes University, Faculty of Science, Department of Computer Science, 2009)
The notion of a global knowledge society is somewhat of a misnomer due to the fact that large portions of the global community are not participants in this global knowledge society which is driven, shaped by and socio-technically biased towards a small fraction of the global population. Information and Communication Technology (ICT) is culture-sensitive and this is a dynamic that is largely ignored in the majority of ICT for Development (ICT4D) interventions, leading to the technological determinism flaw and ultimately a failure of the undertaken projects. The deployment of ICT solutions, in particular in the context of ICT4D, must be informed by the cultural and socio-technical profile of the deployment environments and solutions themselves must be developed with a focus towards context-sensitivity and ethnocentricity. In this thesis, we investigate the viability of a software architectural framework for the development of ICT solutions that are context-sensitive and ethnocentric1, and so aligned with the cultural and social dynamics within the environment of deployment. The conceptual framework, named PIASK, defines five tiers (presentation, interaction, access, social networking, and knowledge base) which allow for: behavioural completeness of the layer components; a modular and functionally decoupled architecture; and the flexibility to situate and contextualize the developed applications along the dimensions of the User Interface (UI), interaction modalities, usage metaphors, underlying Indigenous Knowledge (IK), and access protocols. We have developed a proof-of-concept service platform, called KnowNet, based on the PIASK architecture. KnowNet is built around the knowledge base layer, which consists of domain ontologies that encapsulate the knowledge in the platform, with an intrinsic flexibility to access secondary knowledge repositories. The domain ontologies constructed (as examples) are for the provisioning of eServices to support societal activities (e.g. commerce, health, agriculture, medicine) within a rural and marginalized area of Dwesa, in the Eastern Cape province of South Africa. The social networking layer allows for situating the platform within the local social systems. Heterogeneity of user profiles and multiplicity of end-user devices are handled through the access and the presentation components, and the service logic is implemented by the interaction components. This services platform validates the PIASK architecture for end-to-end provisioning of multi-modal, heterogeneous, ontology-based services. The development of KnowNet was informed on one hand by the latest trends within service architectures, semantic web technologies and social applications, and on the other hand by the context consideration based on the profile (IK systems dynamics, infrastructure, usability requirements) of the Dwesa community. The realization of the service platform is based on the JADE Multi-Agent System (MAS), and this shows the applicability and adequacy of MAS's for service deployment in a rural context, at the same time providing key advantages such as platform fault-tolerance, robustness and flexibility. While the context of conceptualization of PIASK and the implementation of KnowNet is that of rurality and of ICT4D, the applicability of the architecture extends to other similarly heterogeneous and context-sensitive domains. KnowNet has been validated for functional and technical adequacy, and we have also undertaken an initial prevalidation for social context sensitivity. We observe that the five tier PIASK architecture provides an adequate framework for developing context-sensitive and ethnocentric software: by functionally separating and making explicit the social networking and access tier components, while still maintaining the traditional separation of presentation, business logic and data components.
Keywords: Information technology; Expert systems (Computer science); Software architecture; User interfaces (Computer systems); Ethnoscience; Social networks; Rural development; echnical assistance -- Developing countries; Information networks -- Developing countries